Explaining Cross-National Variations in the Prevalence and Character of Undeclared Employment in the European Union - Williams, Colin C. (European Spatial Research and Policy, 2015)
The aim of this article is to evaluate the competing theories that variously explain the greater prevalence of undeclared employment in some countries either as: a legacy of under-development; a result of the voluntary exit from declared employment due to the high taxes, state corruption and burdensome regulations and controls, or a product of a lack of state intervention in work and welfare which leads to the exclusion of workers from the declared economy and state welfare provision. Analyzing the cross-national variations in the prevalence of, and reasons for, undeclared employment across the European Union using evidence from a 2007 Eurobarometer survey, the finding is that undeclared employment is less prevalent and more of the voluntary variety in wealthier, less corrupt and more equal societies possessing higher levels of social protection and redistribution via social transfers. The theoretical and policy implications are then discussed.